приведем к общему знаменателю первую скобку:
Теперь вторую:
Перемножим
Далее:
Это формула разности кубов
приведем к общему знаменателю первую скобку:
Теперь вторую:![\frac{y}{y}-\frac{x}{y}=\frac{y-x}{y}](/tpl/images/0075/0687/6bfb8.png)
Перемножим![\frac{y^2+xy+x^2}{y^2}*\frac{y-x}{y} = \frac{(y^2+xy+x^2)*(y-x)}{y^3}](/tpl/images/0075/0687/99274.png)
Далее:![\frac{(y^2+xy+x^2)*(y-x)}{y^3}*\frac{y^3}{(x-y)*(x^2+xy+y^2)} =-1](/tpl/images/0075/0687/ef47c.png)
Это формула разности кубов![x^3-y^3=(x-y)*(x^2+xy+y^2)](/tpl/images/0075/0687/410a2.png)